Insulin-like growth factor 2 mRNA binding protein 2 regulates proliferation, migration and angiogenesis of keratinocytes by modulating heparanase stability - Shaomin Zhi (Taylor & Francis Group, 2021)
Wound healing is related to proliferation, migration and angiogenesis of keratinocytes. Insulin-like growth factor 2 mRNA binding protein 2 (IGF2BP2) is an important N6-methyladenosine (m6A) reader, which is involved in multiple processes, including wound healing. However, the function and mechanism of IGF2BP2 in keratinocyte processes are largely uncertain. In the present study, expression levels of IGF2BP2 and heparanase (HPSE) were detected by quantitative reverse transcription polymerase chain reaction and western blotting assays. Cell proliferation was investigated with cell counting kit-8 analysis. Cell migration was determined through wound healing assay. Angiogenesis was measured by tube formation assay and vascular endothelial growth factor (VEGF) level using enzyme linked immunosorbent assay. The interaction between IGF2BP2 and HPSE was analyzed by RNA immunoprecipitation, pull-down and luciferase reporter analyses. The results showed that IGF2BP2 expression was enhanced in wound healing. IGF2BP2 downregulation constrained HaCaT cell proliferation, migration and angiogenesis. IGF2BP2 knockdown decreased HPSE expression. IGF2BP2 could regulate HPSE stability by binding with 3ʹ untranslated region (UTR) of HPSE. HPSE upregulation attenuated silencing IGF2BP2-mediated suppression of proliferation, migration and angiogenesis. As a conclusion, IGF2BP2 knockdown repressed proliferation, migration and angiogenesis of HaCaT cells by decreasing HPSE stability.